Utilization of Foot Length as a Non-Invasive Anthropometric Measurement in Neonates Admitted to the NICU in a Tertiary Care Centre in North Karnataka, India - Siddu Charki; Trimal Kulkarni; Vijayakumar Biradar; Mohd Shannawaz; Mallanagouda Patil; Siddarameshwar Kalyanshettar; Shankargouda Patil (Mashhad University of Medical Sciences, 2021)
Background: The majority of the neonates in the Neonatal Intensive Care Unit (NICU) would be on respiratory support either invasive or non-invasive ventilation. Therefore, it is difficult to measure anthropometries, such as weight, length, and head circumference in these sick newborns. This study aimed to determine the correlation of foot length with occipitofrontal head circumference (OFC), crown-heel length (CHL), and weight of the newborn. Methods: A cross-sectional study was conducted at the level IIb NICU of Shri B M Patil Medical College Hospital and Research center, Vijayapur, India. The foot length, OFC, and CHL of the neonates with gestational ages of 28-42 weeks were measured between 12 hours and 7 days of life. Results: Out of 350 neonates enrolled, 61% and 39% of the newborns were preterm and term, respectively. The correlation between foot length and birth weight (r=0.90) and foot length and length (r=0.89) was pronounced in premature neonates. Moreover, a positive linear correlation was observed between foot length and weight in neonates of all gestational ages. To identify the low birth weight (LBW) neonates (<2500 gm), a foot length of less than 7.41 cm had sensitivity and specificity of 94% and 50%, respectively. Furthermore, foot length less than 6.62 cm had 100% sensitivity and 67% specificity to identify the very LBW newborns (<1500 gm). Conclusion: Birth weight and CHL of premature newborns can be estimated from the measurement of foot length that was performed easily and rapidly. Measurement of foot length is valuable in premature neonates who are too ill at birth or those who are on ventilators. Furthermore, foot length may be used in the identification of LBW and VLBW newborns who are admitted to the NICU.